Cytomegalovirus infection associated with atypical bronchopulmonary dysplasia in a preterm neonate: a case report - Zainudin, Zurina; Abang Abdullah, Aisha Fadhilah; Sahadan, Dg. Zuraini (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Cytomegalovirus (CMV) is frequently isolated from neonates. Symptomatic infection is only apparent in 10% of affected babies with particular predilection for the reticuloendothelial and central nervous system. Isolated respiratory system involvement is rarely encountered. We report a case of a premature 32 weeks infant who required prolonged oxygen dependency and treated for bronchopulmonary dysplasia. The diagnosis of CMV pneumonitis was only discovered after detection of CMV DNA in the bronchoalveolar lavage. A high level of clinical awareness is crucial as a definite diagnosis and treatment will significantly alter the morbidity and the cost of therapy.